ARE WE STILL NEGLECTING FATHERS? THE ROLE OF THE FATHER IN FAMILY DYNAMICS AND ITS IMPACT ON FAMILY MEMBER’S PSYCHOLOGICAL WELL - BEING. - Yárnoz Yaben, Sagrario (Anales de Psicología / Annals of Psychology, 2006)
A review of the research carried out on fatherhood in the last 30 years is described in this article. From the first descriptive-comparative studies on how fathers and mothers behave toward their children, the field has progressively grown wider and more complex, in part, reflecting changes occurred in society in the last years and their impact on the distri-bution of men and women’s roles within the family. We analyze the main factors controlling the father’s involvement in child care: family organiza-tion, the mother and father’s work, the attitudes of mothers and fathers, relationships and conflict between parents, and divorce. The last part is devoted to the presence of the father in the area of Clinical Psychology and Developmental Psychopathology. Finally, promising lines of research recently opened in this field are summarized.